1997
DOI: 10.1006/ecss.1996.0121
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Nitrate Uptake Kinetics of Phytoplankton Communities in a Mediterranean Coastal Lagoon

Abstract: Nitrate uptake kinetics of different phytoplankton communities exhibit great variability over a 1-year period. Classical saturation kinetics accompanied by an induction phase are shown by blooms of Chaetoceros sp. in low nitrate waters. Biphasic kinetics, with transition points between 10 and 50 M, are shown by blooms of Skeletonema costatum and flagellates, while unsaturated kinetics (up to 100 M) are shown by Thalassiosira blooms and flagellate blooms. The latter also exhibit surge uptake of nitrate in situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 33 publications
3
47
0
Order By: Relevance
“…In this study we observed classical MichaeliseMenten kinetics for NH 4 but were unable to determine N uptake kinetics for NO 3 , although comparing rates obtained with saturating level of the two DIN species, there was higher V MAx for NO 3 compared to NH 4 . Deviation (to linear or biphasic) from the hyperbolic relationship for NO 3 uptake at saturating to supersaturating concentrations have been described in many algal species including diatoms (Serra et al, 1978;Watt et al, 1992;Collos et al, 1992Collos et al, , 1997Collos et al, , 2005Lomas and Glibert, 1999b) and upwelled phytoplankton . Two studies (Huntsman and Barber, 1977;Lancelot and Billen, 1985) showed that C and N uptake were coupled during linear NO 3 uptake at high concentrations.…”
Section: Maximal No 3 Uptake Exceeds Maximal Nh 4 Uptakementioning
confidence: 99%
“…In this study we observed classical MichaeliseMenten kinetics for NH 4 but were unable to determine N uptake kinetics for NO 3 , although comparing rates obtained with saturating level of the two DIN species, there was higher V MAx for NO 3 compared to NH 4 . Deviation (to linear or biphasic) from the hyperbolic relationship for NO 3 uptake at saturating to supersaturating concentrations have been described in many algal species including diatoms (Serra et al, 1978;Watt et al, 1992;Collos et al, 1992Collos et al, , 1997Collos et al, , 2005Lomas and Glibert, 1999b) and upwelled phytoplankton . Two studies (Huntsman and Barber, 1977;Lancelot and Billen, 1985) showed that C and N uptake were coupled during linear NO 3 uptake at high concentrations.…”
Section: Maximal No 3 Uptake Exceeds Maximal Nh 4 Uptakementioning
confidence: 99%
“…However, our data and a previous report (GIACOBBE et al, 1996) demonstrated the dominance of ammonia in the Bay of Tunis. The assimilation of ammonium by phytoplankton requires a lower metabolic energy than nitrate (COLLOS et al, 1997). EPPLEY et al (1969) asserted that ammonium levels higher than 2 ÌM induced almost maximal inhibition of nitrate uptake by phytoplankton.…”
Section: Species Response To Nutrient Variabilitymentioning
confidence: 99%
“…Field studies have demonstrated that microalgal taxa prefer particular forms of a given nutrient element (Berg et al 1997, 2003a, Lomas et al 1996). For example, Aureococcus anophagefferens has been shown to proliferate faster in NH 4 + or urea-amended water than in water with NO 3 -amendments, while diatoms tend to grow fastest in waters with high NO 3 -fluxes (Berg et al 1997, Collos et al 1997). The present study examines the hypothesis that nitrogen speciation in Long Island embayments controls phytoplankton community composition through resource competition.…”
Section: Introductionmentioning
confidence: 99%